Fabrication of complete dentures with aluminum foil spacer for torus palatinus: a case report - Alifiani, Rizki Indah; Prissynisa, Sarah Taskia; Kunsputri, Fahma Aldihyah; Nursin, Rohmat (Universitas Padjadjaran, 2024)
Introduction: The success of denture fabrication depends on retention and stabilization. The condition known as torus palatinus manifests as a nodular exophytic proliferation of compact bone along the central axis of the hard palate. The large size of the torus palatinus compromises retention and stabilization of dentures. This article describes the prosthodontic treatment for an edentulous patient with a big palatal torus palatinus, utilizing an aluminum foil spacer for the fabrication of a complete denture. Case report: A 69-year-old woman presented to RSGM UMY, reporting difficulty chewing and having all her teeth missing in the arch with a torus palatinus. A maxillary prosthesis was constructed utilizing a spacer that incorporated aluminum foil specifically within the region of the palatine torus. The presence of this bony growth in the palatine region can make the process of creating a complete denture for a patient with a torus palatinus more difficult. The modifications made to ensure patient comfort, functional stability, and optimal denture retention while accommodating the torus are what make the treatment process special. Furthermore, the aluminum foil spacer was designed to provide retention support for the complete denture. Conclusion: To ensure the stability and retention of the complete denture in a patient with a torus palatinus, the impression must generate a vacuum space. In cases of torus palatinus, in addition to employing a window design on the maxillary base plate, an aluminum foil spacer can be utilized over the relief of the torus, with the maxillary base plate covering the torus completely.